Essentials for a health service (London : Communist Party, 1946)
1946 1946 1940s 12 pages steps we have suggested unless a sufficient strength of nursing and auxiliary staff is rapidly made available. We believe the difficulties of providing nurses really fall under two heads: How to retain in nursing all those nurses who are in the Forces and how best to use other grades of nurses, V.A.D.s, nurse auxiliaries, etc. A. This problem is largely one of conditions of service, as we think is now generally agreed. Adult women who are nurses have tolerated conditions which cannot be allowed to continue, however strenuous the obstruction by matrons, nurse administrators and hospital authorities who are steeped in a deep-rooted tradition that no longer serves any useful purpose. We therefore put forward the following suggestions for consideration: (i) The Rushcliffe scales are now inadequate. This applies particularly to ward sisters and trained nurses. Government grants to hospitals paying salaries at Rushcliffe levels should not only be increased with improvements of these scales, but made dependent on the adoption of the 48-hour week at some fixed date. (ii) Trained nurses must be allowed complete independence in their off-duty times, whether living in hospitals or nurses' homes. Trained nurses should be allowed to live out if they wish. (iii) All hospitals receiving monies from public sources should be compelled: (a) to adopt measures for the care of nurses' health on the lines laid down by the King Edward VII Fund; (b) to adopt nurses' representative councils; (c) to allow and encourage nurses to organise themselves in trade unions and professional associations. (iv) A federated superannuation scheme should be arranged for all nurses, allowing for maintenance of rights throughout all changes of jobs. Further, urgent consideration should be given to the problem of loss of superannuation rights of nurses who joined the Forces. (v) Use must be made of married nurses who wish to continue their profession, and there should be no bar to nurses who wish to marry. (vi) Additional recreational and cultural facilities for the staff 7 15X/2/103/357